Gaya Hidup Pada Pasien Hipertensi Di Wilayah Kerja Puskesmas Wates Kabupaten Kulon Progo - Ana Ratnawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2017)
Abstract Hypertension is ‘the silent disease’ because people do not recognize that they have hypertension before cheking up their blood pressure. The number of occurences of this prevalence disease are high in Kulon Progo District. The one of causes of increasing the patient hypertension is lifestyle changes. This research is aimed to know hypertension patients’ lifestyles in Public Health Center in Wates, Kulon Progo District. This research is a descriptive qualitative using surveys as a method of collecting data. The samples used as objects of the study consist of 455 people, incidental samplings as a technique of obtaining data are 213 people, and this study employs a data instrument in the form of enclosed questionnaires. The data analysis was done descriptively adopting mean formula. Next, the data were classified by using percentage formula. Hypertension patients’ lifestyles in Public Health Center in Wates, Kulon Progo which are mainly categorized as healthy are 178 people (83,57%); healthy dietary habit comprises 163 people (76,53%) for health category; physical activities or sports are 193 people (90,61%) classified as healthy; smoking habit is 151 people (70,89%) categorized as unhealthy since there are patients smoking and breathing smoke. Last, stress management is 173 people (81,22%) classified as healthy. Lifestyles of hypertension patients in Public Health Center in Wates, Kulon Progo that majority is classified as healthy. Keywords : Lifestyles, hypertension disease